1993
DOI: 10.1089/neu.1993.10.201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nimodipine on Posttraumatic Spinal Cord Ischemia in Baboons

Abstract: Posttraumatic ischemia appears to be largely responsible for the extension of lesions in acute injury of the spinal cord. In the present study, we have evaluated the putative improvement of axonal function by the calcium channel blocker nimodipine after acute trauma of the spinal cord. Three techniques were used: (1) spinal cord blood flow (SCBF) using a scanographic technique with stable xenon, (2) somatosensory evoked potentials (SEPs), and (3) magnetic resonance imaging (MRI). Thirteen baboons were used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Several reports have suggested the efficacy of nimodipine in increasing SCBF following spinal cord injury [9,22], although some reports have failed to demonstrate any efficacy [8,12]. Nimodipine induces relaxation of cerebral vessels in in vivo and in vitro preparations [1,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have suggested the efficacy of nimodipine in increasing SCBF following spinal cord injury [9,22], although some reports have failed to demonstrate any efficacy [8,12]. Nimodipine induces relaxation of cerebral vessels in in vivo and in vitro preparations [1,28].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on spinal cord blood flow (SCBF) have already been performed. Based on these studies, calcium channel antagonists such as nimodipine have attracted attention as possible agents for improving SCBF [9,22], although some authors have reported no beneficial effect of nimodipine on axonal function [12]. More work is needed to determine how the vessels of the spinal cord react following injury.…”
Section: Introductionmentioning
confidence: 99%
“…In various studies, nimodipine used in the treatment of laryngeal nerve injury is shown to accelerate recovery period, and this is supported by objective measurements (EMG). [28][29][30] Pointillart et al [31] defined the therapeutic effect of 1week nimodipine administration on spinal cord injury by increasing blood flow. He stated significant improvement in neurologic signs after administering methylprednisolone and nimodipine to 100 patients with spinal cord injury in…”
Section: Ent Updatesmentioning
confidence: 99%
“…28 Nimodipine also supported spinal cord blood flow when used in baboons with compressive spinal cord lesions at a dosage of 0.02 mg/kg/hour for 2 hours and then 0.04 mg/kg/hour for 1 week. 46 Neither of these studies evaluated functional recovery. Other groups, using similar injury models and comparable drug regimes, have been unable to demonstrate a beneficial effect of nimodipine in spinal cord injury, bringing the efficacy of nimodipine into question.…”
Section: Biochemical Eventsmentioning
confidence: 99%